2013
DOI: 10.1016/b978-0-444-63327-9.00017-5
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Interventions to Enhance Broad Cognitive Abilities and Prevent Dementia

Abstract: Process-based cognitive trainings (PCTs) and novelty interventions are two traditional approaches aiming to prevent cognitive decline and dementia. However, both have their limitations. PCTs improve performance only in cognitive tests similar to the training tasks with inconsistent transfer effects on dissimilar tests. We argue that this learning specificity is due to a low training task variability. Novelty interventions are characterized by a high task variability but do not target specific processing demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 157 publications
3
81
1
3
Order By: Relevance
“…In line with this notion, Angevaren and colleagues [5] demonstrated that cognitive function was associated with the number of different physical leisure activities, but not with the time spent with physical exercise per week. Finally, an active lifestyle comprises activities of different domains such as physical and cognitive activities, which may have synergistic effects on cognition [27]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this notion, Angevaren and colleagues [5] demonstrated that cognitive function was associated with the number of different physical leisure activities, but not with the time spent with physical exercise per week. Finally, an active lifestyle comprises activities of different domains such as physical and cognitive activities, which may have synergistic effects on cognition [27]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the applied training tasks were often quite similar to the outcome measures in the studies, and training effects were restricted to the trained domain [23, 24]. There is an intensive debate on the extent to which improvements through training generalize to broader cognitive constructs, and especially to everyday cognitive functioning [2527]. Lately, a novel cognitive training approach was developed, based on principles of neuroplasticity [28].…”
Section: Introductionmentioning
confidence: 99%
“…Dancing may be considered an ideal example of what multimodal training should consist of, due to combining physical and cognitive activity together ( Fissler et al, 2012 ; Kraft, 2012 ; Olsson, 2012 ) in an enriched environment ( Kattenstroth et al, 2010 ). Aside from the physical activity that dancing requires, it also involves various cognitive functions such as perception, emotion, executive functioning, memory and motor skills ( Foster, 2013 ).…”
Section: Dance and Neurorehabilitationmentioning
confidence: 99%
“…Engaging specific cognitive resources to execute a specific motor task (e.g., resistance exercise such as squatting) is deemed a necessary prerequisite to guide the facilitation effects of physical exercises. The latter provides the basis for cognitive improvements in response to physical training interventions [8]. However, to our current knowledge, there is currently no study that investigated the cognitive resources needed to execute dynamic resistance exercises (e.g., squats).…”
Section: Introductionmentioning
confidence: 99%